Rules, Preferences and Evolution from the Family Angle - Alessandro Cigno (Institute of Labor Economics (IZA), 2021)
This paper reviews the literature concerning the evolution of cultural traits in general and preferences in particular, and the emergence and persistence of rules or norms, from a family perspective. In models where every new person is effectively the clone of an existing one (either a parent or anyone else), there may be evolution only in the demographic sense that the share of the population who hold a certain trait increases or decreases. Evolution in the strict sense of new traits making their appearance occurs in models where the trait characterizing any given member of any given generation is a combination of traits drawn at random from those represented in the previous generation. Preferences may be altruistic or non-altruistic, but individuals may behave as if they were altruistic even if they are not, because a rule or norm may make it in their interest to do so. Evolutionary stability and renegotiation proofness play analogous roles, the former by selecting altruistic preferences, and the latter by selecting cooperation-inducing rules. The existence of population groups recognizable by outward characteristics like ethnicity or religious practice may convey useful information regarding imperfectly observable traits, such as preferences, of direct interest to individuals, but it may also lead individuals to judge others by their group membership rather than by their unobservable individual qualities, and thus to see them as possible foes.
Keywords: Z1; C78; D01; D02; D13; J13; 330; evolution; preferences; rules; socialization; matching; hold-up problem